2002
DOI: 10.1046/j.1365-2400.2002.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of in‐stream acclimatization in post‐stocking behaviour of European grayling in a Swedish stream

Abstract: The post‐stocking behaviour of hatchery‐reared juvenile European grayling, Thymallus thymallus (L.), with in‐stream acclimatization in a pool for 4, 8, and 12 days before release was compared with fish released directly into a 370‐m long seminatural stream during 1995 and 1996. The behaviour of these groups was compared with fish acclimatized for 16 h in a holding pen (0.7 m3) in a more fast‐flowing part of the stream. All fish were released in the experimental stream at the same time. Initially groups of 30 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 14 publications
5
11
1
1
Order By: Relevance
“…Cresswell & Williams (1983) stated that high water velocities resulted in increased downstream migration of acclimated hatchery-reared fish compared with medium water velocities. This observation was confirmed by Thorfve (2002) for in-stream acclimated hatcheryreared European grayling. Fish that were acclimated in fast-flowing parts of the river were more likely to disappear from the study area than those acclimated in slow-flowing pools (Thorfve 2002).…”
Section: Treatmentsupporting
confidence: 73%
See 1 more Smart Citation
“…Cresswell & Williams (1983) stated that high water velocities resulted in increased downstream migration of acclimated hatchery-reared fish compared with medium water velocities. This observation was confirmed by Thorfve (2002) for in-stream acclimated hatcheryreared European grayling. Fish that were acclimated in fast-flowing parts of the river were more likely to disappear from the study area than those acclimated in slow-flowing pools (Thorfve 2002).…”
Section: Treatmentsupporting
confidence: 73%
“…This observation was confirmed by Thorfve (2002) for in-stream acclimated hatcheryreared European grayling. Fish that were acclimated in fast-flowing parts of the river were more likely to disappear from the study area than those acclimated in slow-flowing pools (Thorfve 2002). As discussed above, flood events and passive drift may also account for the different capture rates observed in the 2 years.…”
Section: Treatmentsupporting
confidence: 73%
“…However, this cannot be generalized; observations published by Weiss and Schmutz (1999) indicated that abiotic factors in heterogeneous biotopes substantially affected growth of stocked fish. The possible short-term weight loss reported by Thorfve (2002) in stocked grayling was not observed during the 5 months of the present experiment. Although the condition factor of reared grayling was initially lower, it was equal to that of wild fish at recapture, suggesting that those artificially reared fish that remained in the experimental sections adapted to local conditions.…”
Section: Discussioncontrasting
confidence: 51%
“…The period between release and recapture might also be significant. Thorfve (2002) found a decrease of > 10% from pre‐release mass in stocked T. thymallus after 1 week in the watercourse. Weiss & Schmutz (1999) showed that stocked hatchery‐reared S. trutta had lost 5–25% of their body mass 3 months after release in the stream.…”
Section: Discussionmentioning
confidence: 88%